2008
DOI: 10.3402/rlt.v16i2.10887
|View full text |Cite
|
Sign up to set email alerts
|

Web-based lecture technologies: blurring the boundaries between face-to-face and distance learning

Abstract: Web-based lecture technologies (WBLT) have gained popularity amongst universities in Australia as a tool for delivering lecture recordings to students in close to real time. This paper reports on a selection of results from a larger research project investigating the impact of WBLT on teaching and learning. Results show that while staff see the advantages for external students, they question the extent to which these advantages apply to internal students. In contrast both cohorts of students were positive abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 6 publications
1
52
1
3
Order By: Relevance
“…In a survey of staff at the University of Tasmania it was estimated that the use of WBLT resulted in a drop in attendance of between 10% and 33% (McKinlay, 2007). An associated concern for some academics is the belief that internal students who aim to utilise WBLT will not exhibit the self-discipline required to keep up to date with the recordings and other course work, and will leave it all until just before the exams (Woo, Gosper, McNeill, Preston, Green & Phillips, 2008). The idea that WBLT results in low attendance rates has, however, been called into question by other research including that by and von Konsky et al (2009), who argue that other factors contribute to falling attendance rates.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…In a survey of staff at the University of Tasmania it was estimated that the use of WBLT resulted in a drop in attendance of between 10% and 33% (McKinlay, 2007). An associated concern for some academics is the belief that internal students who aim to utilise WBLT will not exhibit the self-discipline required to keep up to date with the recordings and other course work, and will leave it all until just before the exams (Woo, Gosper, McNeill, Preston, Green & Phillips, 2008). The idea that WBLT results in low attendance rates has, however, been called into question by other research including that by and von Konsky et al (2009), who argue that other factors contribute to falling attendance rates.…”
Section: Introductionmentioning
confidence: 85%
“…In a survey of second year accounting students at Macquarie University, McElroy & Blount (2006) also noted that students expect value for money in the services provided by their tertiary institution, including the provision of lecture recordings. Woo et al (2008) found that staff perceived advantages for external students using WBLT, but questioned the extent to which these advantages applied to internal students. Woo et al (2008) also found that students were positive about the benefits of WBLT for their learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, some studies have reported that, in the use of blended learning for learning activities, not all students are able to study independently the content provided. For example, students stop to watch video lectures posted on website or LMS because of uninterested and tedious (Woo, Gosper, McNeill, Preston, Green, & Phillips, 2008).…”
Section: The Challenges Of Implementing Blended Learningmentioning
confidence: 99%
“…For the most part, it has been reported that the use of supplementary on-line materials has a positive impact on students' marks at university (e.g., see Williams, Birch & Hancock, 2012;Woo et al, 2008;Gerber, Grundt & Grote, 2007;Mallik, 2011;Morris & Walker, 2006;Gosper et al, 2007 andCatley, 2004). For example, the findings by Mallik (2011) indicate that students' marks in a university unit increased by approximately 0.15 percent for every time they logged into the unit's webpage.…”
Section: Introductionmentioning
confidence: 99%